2022
DOI: 10.3390/nu14112358
|View full text |Cite
|
Sign up to set email alerts
|

11β-HSD1 Inhibitor Alleviates Non-Alcoholic Fatty Liver Disease by Activating the AMPK/SIRT1 Signaling Pathway

Abstract: We investigated the effect of an 11β-HSD1 inhibitor (H8) on hepatic steatosis and its mechanism of action. Although H8, a curcumin derivative, has been shown to alleviate insulin resistance, its effect on non-alcoholic fatty liver disease (NAFLD) remains unknown. Rats were fed a high-fat diet (HFD) for 8 weeks, intraperitoneally injected with streptozotocin (STZ) to induce NAFLD, and, then, treated with H8 (3 or 6 mg/kg/day) or curcumin (6 mg/kg/day) for 4 weeks, to evaluate the effects of H8 on NAFLD. H8 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Some studies have found that CUR can prevent tumor angiogenesis and cell proliferation, induce cancer cell apoptosis, downregulate epidermal growth factor receptor (EGFR) activity and human epidermal growth factor receptor 2 (HER2) expression levels, downregulate nuclear transcription factor, inhibit the activation of the STAT3 signaling pathway, downregulate the expression level of cyclooxygenase 2 (COX-2), and reduce the synthesis level of MMP9 and inducible nitric oxide synthase (iNOS), thus exerting its antitumor effect through multiple pathways [ 14 , 15 ]. However, the application of CUR is constrained by its low water solubility, ease of aqueous solution hydrolysis, clear first-pass elimination effect and low bioavailability [ 16 ]. Obtaining CUR analogs or derivatives through molecular structure modification can well improve the bioavailability of drugs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that CUR can prevent tumor angiogenesis and cell proliferation, induce cancer cell apoptosis, downregulate epidermal growth factor receptor (EGFR) activity and human epidermal growth factor receptor 2 (HER2) expression levels, downregulate nuclear transcription factor, inhibit the activation of the STAT3 signaling pathway, downregulate the expression level of cyclooxygenase 2 (COX-2), and reduce the synthesis level of MMP9 and inducible nitric oxide synthase (iNOS), thus exerting its antitumor effect through multiple pathways [ 14 , 15 ]. However, the application of CUR is constrained by its low water solubility, ease of aqueous solution hydrolysis, clear first-pass elimination effect and low bioavailability [ 16 ]. Obtaining CUR analogs or derivatives through molecular structure modification can well improve the bioavailability of drugs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 3 weeks of treatment, all mice were euthanized, and their blood and primary organs were collected. [ 85 ] The main organs were embedded in paraffin and stained with hematoxylin and eosin for pathomorphological assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Protein expression was quantified and normalized to β‐Actin expression (1:1000, Cell Signaling, Shanghai, China). [ 85 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AMP-activated protein kinase (AMPK)/silent information regulator 1 (SIRT1)/peroxisome proliferator-activated receptor γ coactivator 1α (pGC-1α) pathway is closely associated with cellular energy metabolism, glucose metabolism, and oxidative damage. AMPK is a serine/threonine protein kinase that is activated primarily by regulation in response to cellular energy deficiency. Activated AMPK then sequentially activates SIRT1 and pGC-1α, which play key regulatory roles in mitochondrial biosynthesis, mitochondrial dynamics, energy metabolism, and resistance to oxidative stress. Mitochondrial dynamics, including mitochondrial fusion and fission, along with mitochondrial biosynthesis maintain the normal biological function of mitochondria.…”
Section: Introductionmentioning
confidence: 99%